2022
DOI: 10.3390/ijerph192114483
|View full text |Cite
|
Sign up to set email alerts
|

Mothering a Child with ADHD in the Ultra-Orthodox Community

Abstract: Mothers of children with ADHD are at risk for negative health outcomes. The socio-cultural environment and everyday experiences in life roles may influence psychological health and quality of life. The ultra-orthodox Jewish (UOJ) community is an insular community who is underrepresented in the research, and as such there are no studies exploring the experience of mothering a child in this community. Thus, this study aims to explore the lived experience of mothering a child with ADHD in the UOJ community. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Therefore, UO cultural attitudes and socioeconomic status commonly affect their participation in daily activities, as well as their quality of life, health, and community services. For example, a recent study [27] that explored the live experiences of mothering a child with ADHD, using semi-structured in-depth interviews, found that the perception of their maternal role, social factors, and legitimacy of self-care highlighted the unique impact of the UO culture on the mothers' lived experience. The findings of the current research relating to the UO community [24,27] can likewise highlight the need to promote culturally sensitive health care and interventions for the UO population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UO cultural attitudes and socioeconomic status commonly affect their participation in daily activities, as well as their quality of life, health, and community services. For example, a recent study [27] that explored the live experiences of mothering a child with ADHD, using semi-structured in-depth interviews, found that the perception of their maternal role, social factors, and legitimacy of self-care highlighted the unique impact of the UO culture on the mothers' lived experience. The findings of the current research relating to the UO community [24,27] can likewise highlight the need to promote culturally sensitive health care and interventions for the UO population.…”
Section: Introductionmentioning
confidence: 99%